Wage inequality consequences of expanding public childcare - Lukas Riedel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This paper assesses the impact of a large expansion of public childcare in Germany on wage inequality. Exploiting regional variation in childcare supply over the 1990s, I show that in regions with stronger increases in childcare, wage inequality among women increased less strongly compared to regions with smaller increases. This is primarily driven by the lower half of the wage distribution and qualitatively similar for full- and part-time workers. Larger expansions in childcare, however, do not contribute to a further closing of the gender wage gap.
Keywords: J13; J16; J31; J82; 330; wage inequality; childcare; gender wage gap